Grupo pequeño de personas. (UNED, 2024)
Aparece reunidos en una mesa, de derecha a izquierda en primer lugar Sergio Flores Álvarez, Ronald García Soto, Chester Zelaya Goodman, Jorge Enrique Guier Esquivel, Enrigue Góngora Trejos, Fernando Castro Ramírez